THE RECOMMENDATION OF STERILIZATION SYSTEM OF FURNITURE AS A PROTECTION DURING PANDEMIC ERA IN CAFE DINING AREA - Nurul Audrey; Zalfa Sahira Aristawidya; Rininta Flora Ramadhianti; Vika Haristianti (Ide dan Dialog Desain Indonesia (Idealog), 2022)
This research proposes to recommend the sterilization system for furniture in cafe dining area as a protection in the pandemic era. Entering the new normal era where Health protocol regulations are violated, especially in public areas, such as cof ee shops. Because the level of looseness of regulations in cafes is frightened by the increasing spread of the Covid-19 Virus in the cafe area, this sterilization system is intended to overcome visitors and cafe owners who are lacking and indif erent to the rules of Health protocols, without having to distress anyone. By utilizing the furniture in the cafe because these objects allow direct contact with humans. The selection of the sterilization system used also adjusts to the material used in the furniture and is safe if humans come into direct contact. This research is empirical research. The research method used in this study uses Human Centered Design (HCD) with three design stages that’s are, inspiration, ideation and implementation, where the method focuses on design with the needs of the surrounding human, so far this research is still in the ideation, still in the development of concept ideas. The case studies are cafes and restaurants in the area of Jl. Yos Sudarso no. 3A Tanjung Pinang, Riau Islands, namely Donut's House. The results obtained in the form of furniture that is able to sterilize the area and a layout recommendation that is in accordance with health protocol regulations. Keywords : New Normal, Sterilization, Protection, Caf